2020
DOI: 10.2147/dmso.s283270
|View full text |Cite
|
Sign up to set email alerts
|

<p>Metabolic Syndrome Among Working Adults in Eastern Ethiopia</p>

Abstract: Purpose Metabolic syndrome (MetS) has become a public health challenge in low-income countries due to changing lifestyle and the food environment. However, studies on the prevalence of metabolic syndrome and associated factors are limited in Ethiopia. Therefore, this study assessed the prevalence of MetS and its associated factors among working adults in eastern Ethiopia. Methods A cross-sectional study was conducted involving 1,164 working adults from December 2018 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 49 publications
8
14
0
1
Order By: Relevance
“…The finding suggested that no significant difference was found between night shift workers and day workers in all age groups and all working year subgroups. The prevalence of metabolic syndrome was increased by age and working years, which was consistent with previous studies [ 6 , 39 ]. We did the analysis between night shift workers and metabolic syndrome and its components, the result insisted that NSW was not associated with a higher risk of metabolic syndrome.…”
Section: Discussionsupporting
confidence: 92%
“…The finding suggested that no significant difference was found between night shift workers and day workers in all age groups and all working year subgroups. The prevalence of metabolic syndrome was increased by age and working years, which was consistent with previous studies [ 6 , 39 ]. We did the analysis between night shift workers and metabolic syndrome and its components, the result insisted that NSW was not associated with a higher risk of metabolic syndrome.…”
Section: Discussionsupporting
confidence: 92%
“…All included studies were employed by cross-sectional study design. Of these, five studies were community-based, whereas 15 were institutional-based cross-sectional studies: six studies in Amhara ( 25 , 33 37 ), five studies in Addis Ababa ( 38 – 42 ), three studies in Tigray ( 43 45 ), two studies in Oromia ( 46 , 47 ), two studies in Dire Dawa ( 26 , 48 ), one study in Southern Nations Nationalists and Peoples Region ( 49 ), and one study in Harari ( 50 ). The sample sizes ranged from 225 to 1,935.…”
Section: Resultsmentioning
confidence: 99%
“…After stratifying per the size of their respective department staffs, we included 1,200 employees from the nine colleges and one institute in the university using simple random sampling technique and each participant was selected based on the proportion to the size of their respective departments. Similar techniques of sampling and data collection procedures have been employed in the previous studies [ 24 ] ( Fig 1 ).…”
Section: Methodsmentioning
confidence: 99%